Principles of Drug Therapy in Dentistry - Ali Hussain; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2012)
The book is designed for undergraduates to get to know about the common drugs used in dentistry and to introduce the proper way of their use. It uses simple and easy language, emphasizing important topics in both pharmacology and oral medicine. The idea is to provide a complete understanding that although used in dentistry, drugs are not the main therapeutic measure. Doses and several brand names have been provided with each drug just to be familiar with this way of dealing with drugs. The book described the most important subjects regarding drug use in dentistry. It also provides brief description of drug interaction and some examples of interactions are provided at the end of each chapter. The first chapter discusses all types of dental pain and their characters, pathogenesis of inflammation and its body response and influence. The second chapter is concerned with all antimicrobial agents treating bacterial diseases either prophylactic or curative, and specific or nonspecific. The third and fourth chapters deal with antifungal and antiviral agents in common use, putting in consideration$1 (Bthe indications, contraindications, side effects and drug interactions for each drug. The fifth chapter is the most important one, because an emergency is a life-threatening condition. Dentists should know very well how to deal, manage and take prompt action in such a way to save patient$1 (Bs life. This book useful for all physicians, pharmacists, and before all dentists should keep that chapter as a booklet for emergency cases.s
Keywords: Pharmacology; Electronic books